GLOBAL MARKET EXPANSION: SUSTAINABLE MARKETING STRATEGIES FOR ROPE PRODUCTS - Wibowo, Bambang Sri; Nugroho, Dodit Cahyo (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to analyze in depth the marketing strategies implemented by Jaya Abadi (JA) in an attempt to promote its refinery products in the global market. Through a qualitative approach combining literature reviews and in-depth interviews, this study concludes that JA has implemented an integrated segmentation, selection, and positioning strategy to reach the global market. In addition, the company has established an effective distribution network, both locally and internationally. The results show that refinery products have significant competitive advantages, namely strength, durability, and respect for the environment. These advantages align with global market trends, which increasingly favor sustainable products. The economic analysis shows that using raffia is good for the environment and can also increase a company's profitability. Therefore, this study concludes that raffia has great potential as an alternative sustainable packaging material and could open up greater opportunities in the global market. Further research is recommended to explore more specific practical applications and the commercial potential of raffia.